Photon diffusion in microscale solids. (3rd June 2019) - Das, Avijit; Brown, Andrew K; Mah, Merlin L; Talghader, Joseph J
Abstract: This paper presents a theoretical and experimental investigation of photon diffusion in highly absorbing microscale graphite. A Nd:YAG continuous wave laser is used to heat the graphite samples with thicknesses of 40 μ m and 100 μ m. Optical intensities of 10 kW cm −2 and 20 kW cm −2 are used in the laser heating. The graphite samples are heated to temperatures of thousands of kelvins within milliseconds, which are recorded by a 2-color, high speed pyrometer. To compare the observed temperatures, differential equation of heat conduction is solved across the samples with proper initial and boundary conditions. In addition to lattice vibrations, photon diffusion is incorporated in the analytical model of thermal conductivity for solving the heat equation. The numerical simulations showed close matching between experiment and theory only when including the photon diffusion equations and existing material properties data found in the previously published works with no fitting constants. The results indicate that the commonly-overlooked mechanism of photon diffusion dominates the heat transfer of many microscale structures near their evaporation temperatures. In addition, the treatment explains the discrepancies between thermal conductivity measurements and theory that were previously described in the scientific literature.